Tindak Tutur Ekspresif Dalam Novel Cinta Suci Zahrana Karya Habiburrahman El Shirazy - Niken Jeniska; Siti Ainim Liusti (Persona: Kajian Bahasa dan Sastra, 2023)
The two topics covered in this study are: (1) the usage of diverse expressive speech actions in Habiburrahman El Shirazy's Cinta Suci Zahrana novel and (2) the speech act techniques employed in the novel. The novel Cinta Suci Zahrana by Habiburrahman El Shirazy's expressive utterances served as the study's source of data. It uses qualitative data. The data collection techniques in this study were: (1) recognizing and analyzing the context of the discussion that includes expressive speech acts in the book Cinta Suci Zahrana by Habiburrahman El Shirazy, (2) determining the intent and purpose of the utterances conveyed by speakers according to the speech situation, (3) comprehending and evaluating the speech patterns utilized by the characters in the book Cinta Suci Zahrana by Habiburrahman El Shirazy, (4) Making a list of the expressive speech acts utilized by the characters in Habiburrahman El Shirazy's Cinta Suci Zahrana. Additionally, the following steps were taken in the analysis of the data in this study: (1) identify data on the variety of expressive speech acts and speech strategies obtained, (2) classify the data based on research objectives, and (3) linking the data analyzed with the theory used in research. This study came to two conclusions. In the book Cinta Suci Zahrana, there are six different categories of expressive speaking acts. Second, Habiburrahman El Shirazy's Cinta Suci Zahrana employs five speech-acting techniques.